2014
DOI: 10.1097/ede.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Phenols and Growth in Boys

Abstract: Background Phenols interact with nuclear receptors implicated in growth and adipogenesis regulation. Only a few studies have explored their effects on growth in humans. Objectives We studied the associations of maternal exposure to phenols during pregnancy with prenatal and postnatal growth of male newborns. Methods Within a cohort of women recruited during pregnancy, we selected 520 mother–son pairs and quantified 9 phenols in spot urine samples collected during pregnancy. We used ultrasonography during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
173
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(192 citation statements)
references
References 34 publications
(55 reference statements)
10
173
8
1
Order By: Relevance
“…For example, the significant association between prenatal TCS and head circumference in the Lassen et al (2016) study was observed in boys, but not girls; the two other studies limited to boys (Philippat et al , 2014 reported null results, as did the two studies that examined boys and girls together Geer et al 2017).…”
Section: Birth Outcomesmentioning
confidence: 91%
See 4 more Smart Citations
“…For example, the significant association between prenatal TCS and head circumference in the Lassen et al (2016) study was observed in boys, but not girls; the two other studies limited to boys (Philippat et al , 2014 reported null results, as did the two studies that examined boys and girls together Geer et al 2017).…”
Section: Birth Outcomesmentioning
confidence: 91%
“…Consider, for example, a study from the French EDEN mother-child cohort (Philippat et al 2014). The study included children of both sexes, but the results were presented for boys only.…”
Section: Consistency Of Methods Results and Reporting Across Studiesmentioning
confidence: 99%
See 3 more Smart Citations